Pengajuan Gugatan Terhadap Ayah Kandung Atas Tidak Diberikannya Nafkah Untuk Anak Pasca Perceraian Ditinjau Menurut Hukum Islam Dan Undang-Undang Perkawinan : Studi Kasus Putusan Pengadilan Negeri Salatiga Nomor 102/PDT.G/2021/PN. SLT - Revaganesya Abdallah; Djanuardi Djanuardi; Betty Rubiati (Jurnal Hukum dan Sosial Politik, 2024)
Divorce has legal consequences for the relationship between husband and wife, property, and children resulting from the marriage. Especially for children from marriage, it gives parents the obligation to maintain and educate their children. However, specifically child maintenance after divorce according to Islamic Law and the Marriage Law is the obligation of a father to his child. Case Study Research on Salatiga District Court Decision Number 102/PDT.G/2021/PN. Slt. a child filed a lawsuit against his father for post-divorce maintenance, however, the lawsuit was rejected by the Panel of Judges of the Salatiga District Court. Therefore, this study aims to determine the responsibility for fulfilling the father's maintenance of a child after divorce and the legal remedies that a child can take when the right to post-divorce maintenance is not fulfilled by using the research method, namely, the normative juridical approach method and analytical description research specifications, namely to examine events as the object of research guided by primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis method uses qualitative juridical which results in descriptive data analysis.